2020
DOI: 10.1101/2020.09.16.297366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bromelain Inhibits SARS-CoV-2 Infection in VeroE6 Cells

Abstract: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The initial interaction between Transmembrane Serine Protease 2 (TMPRSS2) primed SARS-CoV-2 spike (S) protein and host cell receptor angiotensin-converting enzyme 2 (ACE-2) is a pre-requisite step for this novel coronavirus pathogenesis. Here, we expressed a GFP-tagged SARS-CoV-2 S-Ectodomain in Tni insect cells. That contained sialic acid-enriched N- and O-glycans. Surface resonance plasmon (SPR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…It is a glycoprotein with an oligosaccharide in its molecular structure. It was shown recently that bromelain inhibits SARS-CoV-2 infection in VeroE6 Cells [66]. It seems that our findings are consistent with these results.…”
Section: Nhcsupporting
confidence: 94%
See 1 more Smart Citation
“…It is a glycoprotein with an oligosaccharide in its molecular structure. It was shown recently that bromelain inhibits SARS-CoV-2 infection in VeroE6 Cells [66]. It seems that our findings are consistent with these results.…”
Section: Nhcsupporting
confidence: 94%
“…To check how our findings correlate with the known compounds for COVID-19 treatment, several of them have been analyzed briefly. We directed attention to Chloroquine, Emodin, β-D-N4-Hydroxycytidine (NHC), bromelain, luteolin [61][62][63][64][65][66], and tetra-O-galloyl-β-d-glucose (TGG) [59].…”
Section: Chemical Structures Of the Antiviral Compoundsmentioning
confidence: 99%
“…In our study, we showed for the first time a biochemical link between LL-37 and the SARS-CoV-2 S protein and provide a rationale for the use of vitamin D in infection prophylaxis, and for therapeutic administration in the treatment of COVID-19 patients. Peptide based therapeutics, especially antimicrobial peptides, are excellent drug candidates as they have little adverse effects and show anti-coronavirus activity [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its nutritional value, bromelain’s active ingredients have been shown to have therapeutic properties, such as antiviral (e.g. anti-SARS-CoV-2), anti-inflammatory, anticancer, antimicrobial, and immunomodulatory function ( Dopheide and Ward, 1981 ; Chandler and Mynott, 1998 ; Rathnavelu et al, 2016 ; Sagar et al, 2020 ; Chakraborty et al, 2021 ). Bromelain has a half-life of 6–9 h ( Castell et al, 1997 ) and a plasma concentration of 2.5–4 ng/ml after an oral dose of 8.6 g per day ( Kumakura et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%